Dimerization of conserved ascaroside building blocks generates species-specific male attractants in Caenorhabditis nematodes. - Dong, Chuanfu; Dolke, Franziska; Bandi, Siva; Paetz, Christian; Von Reuss, Stephan (My University, 2020)
Comparative ascaroside profiling of Caenorhabditis nematodes using HPLC-ESI-(-)-MS/MS precursor ion scanning revealed a class of highly species-specific ascaroside dimers. Their 2- and 4-isomeric, homo- and heterodimeric structures were identified using a combination of HPLC-ESI-(+)-HR-MS/MS spectrometry and high-resolution dqf-COSY NMR spectroscopy. Structure assignments were confirmed by total synthesis of representative examples. Functional characterization using holding assays indicated that males of Caenorhabditis remanei and Caenorhabditis nigoni are exclusively retained by their conspecific ascaroside dimers, demonstrating that dimerization of conserved monomeric building blocks represents a yet undescribed mechanism that generates species-specific signaling molecules in the Caenorhabditis genus.